New approaches to early diagnosis of arthrosis and prospects for its pathogenetic therapy - Lilia Vladimirovna Luchikhina (Современная ревматология, 2014)
Objective: to study the possible chondroprotective effect of the viscoelastic agent synvisc, by applying the developed methodological and classification approaches to evaluating the intraarticular cartilage by arthroscopy and magnetic resonance imaging (MRI).Subjects and methods. Eighty six patients with knee arthrosis were examined and divided into 2 groups: a study group of 64 patents and a control one of 22 patients. Synvisc was injected into the affected joint in the study group; methylprednisolone acetate in the control group. Arthroscopic and MRI criteria were used to evaluate the articular cartilage. Arthroscopy and MRI were performed before and 6 and 12 months after treatment.Results. The developed methodological approaches are distinguished for their high sensitivity (89.7%) and specificity (95.2%), which could estimate changes in arthrosis just at the stage of hyperhydration and dechondral changes and monitor long the chondroprotective effect of synvisc. The agent was noted to have a positive effect at the stage of hyperhydration and dechondral changes and in grade I–II intrachondral changes and to be able to prevent or stop the progression of OA in later (II–III) X-ray stages. The effect of synvisc did not depend on disease duration and patient age, but it decreased in the presence of marked articular anatomic and morphological changes. The administration of the agent could reduce or preclude the use of nonsteroidal anti-inflammatory drugs or intraarticular glucocorticoids n 96% of cases.Conclusion. Arthroscopy and MRI make possible to recognize arthrosis in its earliest stage and to monitor the effect of drugs on the cartilage. The use of synvisc in early-stage gonarthrosis allows a long-term symptomatic effect and some structure-modifying activity.